2021
DOI: 10.1186/s12576-021-00823-z
|View full text |Cite|
|
Sign up to set email alerts
|

Swimming training and Plantago psyllium ameliorate cognitive impairment and glucose tolerance in streptozotocin–nicotinamide-induced type 2 diabetic rats

Abstract: Brain malfunction is common in diabetic patients. On the other hand, a growing body of research points to the beneficial effect of medicinal plants and exercise training on insulin sensitivity and brain function. Therefore, the aim of the present study was to investigate the effect of co-administration of swimming training and Plantago psyllium (mixed with standard pelleted food at a weight ratio of 5%) on learning and memory impairment and glucose tolerance in type 2 diabetic rats. For this purpose, 10 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…It is well known that exercise improves cognitive function, learning ability, and memory function [ 47 , 48 ]. Moreover, it has been shown that physical exercise can enrich memory deficits and social behavior complications and decreases hyperactivity in autism [ [49] , [50] , [51] ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that exercise improves cognitive function, learning ability, and memory function [ 47 , 48 ]. Moreover, it has been shown that physical exercise can enrich memory deficits and social behavior complications and decreases hyperactivity in autism [ [49] , [50] , [51] ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no effective treatment for postoperative cognitive function. Many studies showed that the reductions of neuron number, cognitive related neurotransmitters, and corresponding receptors could cause the decline of cognitive function [ 10 , 11 ]. Other studies showed that surgical trauma was one of the high risk factors for the cognitive dysfunction [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the co-author “Kamal Ranjbar” would like to remove the following affiliation “Neurophysiology Research Center, Hamadan University of Medical Sciences, Hamadan, Iran”.…”
Section: Correction To: the Journal Of Physiological Sciences (2021) ...mentioning
confidence: 99%